The intestinal fatty acid-binding protein as a marker for intestinal damage in gastroschisis - Kokesova, Alena; Coufal, Stepan; Frybova, Barbora; Kverka, Miloslav; Rygl, Michal (PloS one, 2019)
BACKGROUND/PURPOSE: We analyzed the capacity of urinary Intestinal fatty acid-binding protein (I-FABP) to quantify the degree of mucosal injury in neonates with gastroschisis (GS) and to predict the speed of their clinical recovery after surgery. METHODS: In this prospective study, we collected urine during the first 48h after surgery from neonates operated between 2012 and 2015 for GS. Neonates with surgery that did not include gut mucosa served as controls for simple GS and neonates with surgery for intestinal atresia served as control for complex GS patients. The I-FABP levels were analyzed by ELISA. RESULTS: Urinary I-FABP after the surgery is significantly higher in GS newborns than in control group; I-FABP in complex GS is higher than in simple GS. I-FABP can predict subsequent operation for ileus in patients with complex GS. Both ways of abdominal wall closure (i.e. primary closure and stepwise reconstruction) led to similar levels of I-FABP. None of the static I-FABP values was useful for the outcome prediction. The steep decrease in I-FABP after the surgery is associated with faster recovery, but it cannot predict early start of minimal enteral feeding, full enteral feeding or length of hospitalization. CONCLUSION: Urinary I-FABP reflects the mucosal damage in gastroschisis but it has only a limited predictive value for patients' outcome.
Keywords: Intestinal Mucosa; Female; biologické markery; gastroschiza; novorozenec; Biomarkers; Gastroschisis; ženské pohlaví; Predictive Value of Tests; prediktivní hodnota testů; lidé; Fatty Acid-Binding Proteins; Infant, Newborn; proteiny vázající mastné kyseliny; studie případů a kontrol; prognóza; Intestinal Atresia; prospektivní studie; Male; Case-Control Studies; Prospective Studies; atrézie střev; Prognosis; mužské pohlaví; střevní sliznice; Humans